Treatment Trends of Diabetic Macular Edema in Korea (TRACK) Study: A Prospective Multicenter Study - Kim, Min Seok; Joo, Kwangsic; Shin, Yong-Un; Cho, Hee Yoon; Lee, Joo Yong; Sagong, Min; Kim, Jee Taek; Kim, Yu Cheol; Kim, Hyun Woong; Kwak, Hyunduck; Ahn, Seong Joon; Lee, Mee Yon; et al. (Korean journal of ophthalmology, 2025)
Purpose: To evaluate real-world functional and anatomical outcomes, treatment patterns, and ocular examination trends in diabetic macular edema (DME) in Korea.Methods: A prospective, multicenter, observational study was conducted at 17 hospitals (2017–2022) involving adults with DME. Patients were categorized into center-involving DME (CI-DME) and non-CI-DME groups based on optical coherence tomography findings. Serial changes in best-corrected visual acuity (BCVA), central subfoveal thickness (CST), and treatment and examination patterns were recorded at baseline and follow-up visits (6, 12, 18, and 24 months), and analyzed using linear mixed models and paired t-tests.Results: A total of 209 participants (81 female patients, 38.8%; mean age, 60.2 ± 10.8 years) were enrolled. Over 24 months, 10 of 68 non-CI-DME patients (14.7%) developed CI-DME. CST significantly decreased in the CI-DME group (from 419 µm at baseline to 343 µm, p = 0.001), whereas BCVA remained unchanged in both groups. Throughout the 2-year period, the average number of anti–vascular endothelial growth factor (anti-VEGF) injections was 3.1 ± 3.6, while steroid injections averaged 0.7 ± 1.5. The CI-DME group received significantly more anti-VEGF injections compared to the non-CI-DME group (3.8 ± 3.9 vs. 2.0 ± 2.8, p = 0.004). Additionally, the CI-DME group had more frequent visits (15.8 vs. 11.3, p = 0.017) and optical coherence tomography examinations (9.7 vs. 7.4, p = 0.023). The number of anti-VEGF injections decreased in the CI-DME group over time, while the number of visits decreased in both groups.Conclusions: In real-world clinical practice in Korea, the treatment and monitoring frequency for DME was lower than in major clinical trials, potentially contributing to suboptimal visual outcomes.